VD_FINDINFO Décision / 2009 / 227 vom 1. Dezember 2009 - VD Tribunal cantonal (2009)
PROCÈS DEVENU SANS OBJET, RADIATION DU RÔLE | 38 LPGA, 53 al. 3 LPGA, 58 LPGA, 60 al. 1 LPGA, 83 al. 1 LPA-VD, 83 al. 2 LPA-VD, 91 LPA-VD, 94 al. 1 let. c LPA-VD, 99 LPA-VD